Protection, preferential tariff elimination and rules of origin in the Americas. - GARAY, Luis Jorge (1996)
Presents an overview of tariff and preferential trade policies on the importation of goods originating in member countries of integration agreements, as well as the rules and regulations governing the qualification of goods eligible for preferential trade concessions within the context of regional agreements. Outlines the general dynamics of preferential tariff elimination in intra-hemispheric trade and includes an analysis of the rules of origin currently applied in the Americas.